A mesoscopic DPD simulation study on long chain quaternary ammonium gemini surfactant solution. Issue 1 (31st December 2020) - Zhou, Guanggang; Gao, Meng; Deng, Xuejian; Ma, Yue; Mao, Caiju; Li, Gang; Chen, Chaoran; Sun, Xiaoliang; Khalid, Shah; Lu, Guiwu
Abstract: Dissipative particle dynamics (DPD) simulation method is applied to study the aggregation process of quaternary ammonium gemini surfactants in three systems including pure water, water-ethanol and water-oil mixture solution. The results show that DPD simulation can directly observe the formation and evolution of spherical surfactant clusters. In pure water system, higher surfactant concentration leads to form large spherical cluster. In water-ethanol system, additional ethanol molecules can destroy the stable structure of the hydrophobic radical and inhibit the aggregation of surfactant. In water-oil mixture, we find that gemini surfactants distribute in the oil-water interface, and the interfacial tension reduces as surfactant concentration increases. We studied the effect of temperature on critical micelle concentration (CMC) as well as the distribution of surfactants micelle at water-oil interface. Graphical Abstract: uf0001